A Dyadic Investigation of Collaborative Competence, Social Capital, and Performance in Buyer–Supplier Relationships. Issue 2 (1st March 2015) - Whipple, Judith M.; Wiedmer, Robert; K. Boyer, Kenneth
Abstract : As supply chains become increasingly complex, the management of buyer–supplier relationships is essential for achieving superior performance. To enhance external collaborative relationships, many firms are investing in the development of internal relationship management skills. We propose that the development of internal collaborative process competence (CPC) is an important component for improving external collaborative relationships through the creation of social capital. Our research examines the potential for social capital, which is modeled as a second‐order factor consisting of structural, cognitive, and relational capital, to mediate the relationship between CPC and operational performance. Our findings provide insights as to whether internal competence alone is sufficient for improving the operational performance of the relationship. Based on a dyadic comparison of buyers and suppliers, we find that investment in internal CPC without building external social capital does not lead to any improvement in operational performance. However, investment in CPC is beneficial in cases where buyers and suppliers have also built a high level of social capital, which, in turn, leads to desired operational performance for the relationship.